2003
DOI: 10.1038/sj.npp.1300266
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the Serotonin Transporter Exhibit 5-HT1A Receptor-Mediated Abnormalities in Tests for Anxiety-like Behavior

Abstract: The serotonin transporter (5-HTT) regulates serotonergic neurotransmission via clearance of extracellular serotonin. Abnormalities in 5-HTT expression or function are found in mood and anxiety disorders, and the 5-HTT is a major target for antidepressants and anxiolytics. The 5-HTT is further implicated in the pathophysiology of these disorders by evidence that genetic variation in the promoter region of the HTT (SLC6A4) is associated with individual differences in anxiety and neural responses to fear. To furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
203
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(217 citation statements)
references
References 91 publications
(113 reference statements)
14
203
0
Order By: Relevance
“…The phenomenon is consistent with a reduced anxiety-like behavior (ie, increase center time) and increased locomotor exploration (ie, increase horizontal and vertical activities). It has been demonstrated that in exploration-based tests for anxiety-like behaviors, such as the light-dark exploration or emergence tests, animals with anxiety would rather spend more time in the dark compartment (Blanchard et al, 1990;File, 2001;Holmes et al, 2003b). In light-dark exploration tests, the GAT1 À/À mice showed more transitions between light and dark compartments and spent more time in the light compartment than GAT1 + / + mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon is consistent with a reduced anxiety-like behavior (ie, increase center time) and increased locomotor exploration (ie, increase horizontal and vertical activities). It has been demonstrated that in exploration-based tests for anxiety-like behaviors, such as the light-dark exploration or emergence tests, animals with anxiety would rather spend more time in the dark compartment (Blanchard et al, 1990;File, 2001;Holmes et al, 2003b). In light-dark exploration tests, the GAT1 À/À mice showed more transitions between light and dark compartments and spent more time in the light compartment than GAT1 + / + mice.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence test was conducted as described previously (Holmes et al, 2003b;Smith et al, 1998;Takahashi et al, 1989). The apparatus consisted of an opaque black Plexiglas cube (16 Â 16 Â 19 cm 3 ) with an exit (6 Â 4 cm 2 ) on one side at floor level.…”
Section: Emergence Testmentioning
confidence: 99%
“…For instance, serotonin transporter gene knock-out mice had a 50% reduction in serotonin and exhibited decreased feeding behavior in a novel situation, despite the absence of a generalized increase in anxiety (Lira et al, 2003). In another study of 5-HT transporter knockout mice, anxiety and impaired exploration were reported and attributed to 5-HT1A receptors (Holmes et al, 2003). This notion receives support from studies on 5-HT1A knockout mice, which showed decreased exploratory activity and increased fear of aversive environments (Ramboz et al, 1998).…”
Section: Structure -Function Relationshipsmentioning
confidence: 95%
“…17,18 5-HTT knockout mice show behaviours consistent with anxious and depressive traits; they appear reluctant to explore brightly lit spaces or elevated open platforms and give up struggling early when put in an uncomfortable situation. [19][20][21] Interestingly, the difference from wild-type animals in depression-like giving-up ('behavioural despair') is manifest only after repeated exposure to stressors, analogous to repeated or chronic stressful life events in humans. 20 The 5-HTT knockout animals also show exaggerated neuroendocrine reactions to acute stress similar to the HPA axis over reactivity in depressed humans.…”
Section: Animal Modelsmentioning
confidence: 99%
“…22,23 The effect of 5-HTT knockout on anxietyand depression-like behaviours may be mediated by the absence of functional serotonin clearance mechanism during a vulnerable developmental period, 24 but can still be selectively reversed by pharmacological 5HT1A receptor blockage later in life suggesting a life-long modulatory involvement of the serotonergic system. 19 The anxious-depressive phenotype in 5-HTT knockout mice is associated with increased dendritic branching in the 'fear circuit' including the amygdala and limbic cortex. 20 On the other hand, mice with transgenically increased 5-HTT expression appear fearless and explore bright-lit and open spaces more daringly than wild-type animals.…”
Section: Animal Modelsmentioning
confidence: 99%